Creating pairs of exceptional points for arbitrary polarization control: asymmetric vectorial wavefront modulation - Zijin Yang; Po-Sheng Huang; Yu-Tsung Lin; Haoye Qin; Jesús Zúñiga-Pérez; Yuzhi Shi; Zhanshan Wang; Xinbin Cheng; Man-Chung Tang; Sanyang Han; Boubacar Kanté; Bo Li; et al. (Nature Communications, 2024)
Abstract Exceptional points (EPs) can achieve intriguing asymmetric control in non-Hermitian systems due to the degeneracy of eigenstates. Here, we present a general method that extends this specific asymmetric response of EP photonic systems to address any arbitrary fully-polarized light. By rotating the meta-structures at EP, Pancharatnam-Berry (PB) phase can be exclusively encoded on one of the circular polarization-conversion channels. To address any arbitrary wavefront, we superpose the optical signals originating from two orthogonally polarized -yet degenerate- EP eigenmodes. The construction of such orthogonal EP eigenstates pairs is achieved by applying mirror-symmetry to the nanostructure geometry flipping thereby the EP eigenmode handedness from left to right circular polarization. Non-Hermitian reflective PB metasurfaces designed using such EP superposition enable arbitrary, yet unidirectional, vectorial wavefront shaping devices. Our results open new avenues for topological wave control and illustrate the capabilities of topological photonics to distinctively operate on arbitrary polarization-state with enhanced performances.